2018
DOI: 10.1055/a-0668-0962
|View full text |Cite
|
Sign up to set email alerts
|

Diarylheptanoids from Curcuma phaeocaulis Suppress IL-6-Induced STAT3 Activation

Abstract: Three undescribed diarylheptanoids (3: -5: ) and six known curcuminoids (1, 2: , and 6: -9: ) were obtained from the ethyl acetate-soluble fraction of an ethanolic extract of . Their chemical structures and absolute configurations were elucidated by high-resolution electrospray ionization mass spectrometry, nuclear magnetic resonance spectroscopy, circular dichroism spectroscopy, and the modified Mosher's method. Previous studies constructed Hep3B cells stably transfected with pSTAT3-Luc plasmid containing STA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…It has been demonstrated that the Stat3 pathway is implicated in the development of cancer . We next measured the effect of icaritin on the Stat3 pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the Stat3 pathway is implicated in the development of cancer . We next measured the effect of icaritin on the Stat3 pathway.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the Stat3 pathway is implicated in the development of cancer. 15 We next measured the effect of icaritin on the Stat3 pathway. The decreased expressions of p-Stat3 and Bmi-1 were found in both U87 and T98G cells when icaritin (10 or 20 μM) was added to the cultures ( Figure 3A and 3B).…”
Section: Icaritin Suppressed the Stat3 Pathway In Of Gbm Cellsmentioning
confidence: 99%
“…Interestingly, a recent study has reported that curcumin can exhibit significant inhibitory activity on IL-6-induced STAT3 activation with an IC 50 value FIGURE 3 | Snapshot of the browse page. of 1.6 µM, indicating its potential to be a candidate for the treatment of cancer related to the IL-6/STAT3 signaling pathway (Jang et al, 2019). The rest of the predicted targets provide novel potential proteins involved in cancer immunity by curcumin, which deserve to be further validated by experimental assays.…”
Section: Curcuminmentioning
confidence: 99%
“…S16). IC 50 values were calculated by nonlinear regression analysis as described previously [35]. RAW264.7 cell cytotoxicity was evaluated using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay [34].…”
Section: Isolation Of Compounds 1 and 3 Pulverized Stem Ofmentioning
confidence: 99%